PENGARUH MODEL PBL DENGAN PENDEKATAN TARL PADA PENINGKATAN HASIL BELAJAR KELAS 8 D SMPN MODEL TERPADU BOJONEGORO PADA MATA PELAJARAN IPS - Sri Rahayu, Endah; Aunti Sholihah, Farah; Zaini, Zaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The learning process is said to be successful if students are able to achieve predetermined learning goals. This is also influenced by interactions that occur during the learning process in the classroom, including the accuracy of learning models and approaches. Classroom Action Research was carried out with the aim of improving student learning outcomes in social studies subjects using the Probel Based Learning model and the Teaching at The Right Level approach. The research method used is PTK (Classroom Action Research). The application of the Problem Based Learning learning model with the TaRL approach can improve the learning outcomes of students in social studies subjects in class 8D of Bojonegoro Integrated Model Middle School.